Science and Kawruh Jiwa of Ki Ageng Suryomentaram’s Perspective (International Proceedings of Nusantara Raya, 2022)
The purpose of this study is to describe the thoughts of a so-called Javanese philosopher, namely Ki Ageng Suryomentaram regarding knowledge and science. These two things are certainly different, but they are often used interchangeably. Therefore, it is necessary to explain their position. Knowledge is a series of things that the subject encounters, is obtained about the object through the five senses,    often called science, is a collection of knowledge that has been systematized so that it is logical, methodical, theoretical, objective, and universal. The research was carried out using a qualitative method with a descriptive method. Data was collected through literature searches and library research related to the concept of Ki Ageng Suryomentaram's perspective of science. The results showed that the knowledge found by Ki Ageng Suryomentaram was in the form of Kawruh Jiwa. Namely, knowledge that puts forward the aspect of taste or "roso" so that humans understand themselves completely. The discovery of the soul of Ki Ageng Suryomentaram cannot be separated from the Javanese worldview, namely the link between theory and praxis which eventually leads to true wisdom as an ideal of living together.